INTERRELATION OF TYPES OF INTERPERSONAL DEPENDENCE AND PSYCHOLOGICAL WELLBEING AT YOUTHFUL AGE AND EARLY MATURITY - Kamenskiy, P. I. (Modern Psychology, 2019)
This article is devoted to specifics of interrelation of types of interpersonal dependence and psychological wellbeing at youthful age and early maturity. The author shows the updated requirement of consideration of aspect of dependent behavior of the personality in connection with insufficient scientific knowledge in this area, on the one hand and distribution of not chemical dependences at youthful age and early maturity, with another. Features of communications of types of interpersonal dependence and psychological wellbeing are revealed. The interpersonal dependence is considered from a position of its types – destructive super dependence, dysfunctional office and standard dependence. The provided analysis of empirical data showed that types of interpersonal dependence are connected with psychological wellbeing, but this communication has the specifics. At the same time, it is emphasized that the research demands further different aspects studying of destructive super dependence, dysfunctional office and standard dependence.
Keywords: interpersonal dependence, addiction, psychological wellbeing, standard dependence, dysfunctional office, destructive super dependence